IMPLEMENTATION OF PUBLIC INFORMATION DISCLOSURE THROUGH INFORMATION AND DOCUMENTATION MANAGEMENT OFFICER AT PUBLIC BROADCASTING INSTITUTIONS - Pakpahan, Roy Tumpal (Moestopo International Review on Social, Humanities, and Sciences, 2023)
Televisi Republik Indonesia Public Broadcasting Institution (LPP TVRI) is a public broadcasting organization. In LPP TVRI there is an Information and Documentation Management Officer (PPID) whose job is to manage, store and deliver information and documentation to the public. The purpose of this research is to describe the implementation of Public Information Disclosure of Public Broadcasting Institution Televisi Republik Indonesia through the Information and Documentation Management Officer on the Website. The theory used in this research is the theory of policy implementation from Van Meter and Van Horn. The research method used in this research is descriptive qualitative which seeks to provide a comprehensive description of the issues raised in this study. Furthermore, to strengthen the argumentation, the researcher collected data using observation, interview, and documentation methods. The results of this study indicate that the implementation of Public Information Disclosure of the Public Broadcasting Institution of Televisi Republik Indonesia through the Information Management and Documentation Officer on the Website has been running quite well. In the aspect of socialization, it has not run optimally, this is evidenced by the lack of public participation and knowledge about the website ppid.tvri.go.id. In the aspect of implementation, the information on the website has fulfilled the rules of public information disclosure even though there are still some blanks. Researchers concluded that LPP TVRI through PPID in an effort to realize public information disclosure has been running quite well.